Role of Saccharomyces cerevisiae Nutrient Signaling Pathways During Winemaking: A Phenomics Approach - Vallejo, Beatriz; Peltier, Emilien; Garrigós, Victor; Matallana, Emilia; Marullo, Philippe; Aranda, Agustín (Frontiers in Bioengineering and Biotechnology, 2020)
The ability of the yeast Saccharomyces cerevisiae to adapt to the changing environment of the industrial processes lies on the activation and coordination of many molecular pathways. The most relevant ones are the nutrient signaling pathways, which control growth and stress response mechanisms as result of the availability or scarcity of nutrients, therefore giving an ample margin for improvement of yeast biotechnological performance. A standardized grape juice fermentation assay allowed the analysis of mutants for different elements of many nutrient signaling pathways in different conditions (low/high nitrogen and different levels of oxygenation), so the genetic-environment interactions can be analyzed. Results indicate that cAMP dependent PKA pathway has the greatest relevance regardless the fermentation condition, while mutations on TOR pathways have an effect that is dependent on the nitrogen availability. The production of metabolites of interest such glycerol, acetic acid and pyruvate is controlled in a coordinated way by the contribution of several components of different pathways. Ras GTPase Ras2, a stimulator of cAMP production, is a key factor to achieve fermentation, and is also relevant in sensing nitrogen availability. Increasing cAMP concentration by deleting an enzyme devoted to its degradation, phosphodiesterase Pde2, proves to be a good way to increase fermentation speed, offering keys for biotechnological improvement. Surprisingly glucose repression protein kinase Snf1 and Nitrogen Catabolite Repression transcription factor Gln3 have relevance in fermentation even when there is no starvation. Besides, Gln3 has proved to be essential for respiration in several genetic backgrounds, and its presence is required to achieve full glucose de-repression. Therefore, most pathways sense different types of nutrients and only their coordinated action can ensure successful wine fermentation.